Biofeedback-Based Proprioceptive Training to Improve Functional Prerequisites of Dragon Boating in Breast Cancer Survivors - Giuditta Carretti; Angela Dabraio; Mirko Manetti; Mirca Marini (MDPI AG, 2024)
Breast cancer (BC)-related sequelae drastically impact the psychophysical functioning and quality of life of affected women. Adapted physical activity (APA) has proved to effectively counteract these impairments in a non-medicalized framework. In particular, dragon boats are able to promote body functionality, social interaction, and quality of life in BC survivors, but the literature on specific motor gestures is scarce and practice is still based more on a re-educative perspective than a performative one. In this context, the present longitudinal study investigated the benefits of an adapted biofeedback-based sensorimotor training intervention on upper body functionality in a team of dragon ladies. The 8-week intervention was conceived as integrated dry workout sessions led by an APA kinesiologist and applied a novel sensorized proprioceptive device, such as a Libra board. Post-protocol evaluation revealed a significant improvement in bilateral upper limb mobility, core endurance, and trunk stability along with a distress decrease and quality of life enhancement through validated assessment tools. Our findings suggest that integrating biofeedback-based workout sessions can effectively promote upper body functionality in BC survivors practicing dragon boating. Furthermore, our innovative approach could help spread methodological hints able to boost exercise adherence in this target population, thus counteracting cancer recurrence while promoting overall well-being.